Las estrategias lúdicas y su incidencia en el desarrollo del pensamiento lógico en los niños y niñas de educación inicial de la unidad educativa Darío Guevara, del cantón Puerto Quito, provincia de pichincha periodo 2014- 2015 - Pucuna Ruano, Dayana Vanessa (2016)
This research work entitled ludic”LAS ESTRATEGIAS LÚDICAS Y SU INCIDENCIA EN EL DESARROLLO DEL PENSAMIENTO LÓGICO EN LOS NIÑOS Y NIÑAS DE EDUCACIÓN INICIAL DE LA UNIDAD EDUCATIVA DARÍO GUEVARA, DEL CANTÓN PUERTO QUITO, PROVINCIADE PICHINCHA PERIODO 2014- 2015”. It has been structured and developed according to the regulations of the academic system of the National University of Loja. Was determined as the central problem how affect recreational strategies in the development of logical thinking in children early education of the educational unit Dario Guevara? Its general objective is to know the importance of using recreational strategies and how this affects the development of logical thinking of children early education of the Education Unit Dario Guevara Canton Puerto Quito, Pichincha province, during the academic year 2014 -2015. It was determined as relevant conclusions of the investigative process that 100 % of teachers of children Initial education educational unit investigated, also the observation guide was used to assess the development of logical thinking. It was determined as relevant conclusions of the investigative process that teachers do not know that playful strategies applied in the learning process early education to develop logical thinking, as well as the results can confirm 5 that 100% of pre-school teachers have not trained in play techniques, and that 100% of the authorities do not follow advice or teachers. Against this recommendations were established as The teachers participate in a training seminar on the use of play techniques and the authorities should provide advice and track teachers of Education Initial to apply play techniques, also used in the process Early Childhood Education teaching and learning recreational games, tell stories and graphics manipulation of objects of different colors and shapes to develop logical thinking in children. We recommend designing a proposal to train pre-school teachers in the application of technology Playful, to develop logical thinking of children. Recommending the authorities and teachers after the guide designed to apply immediately, intending to become a functional and viable practical tool in solving the issues raised.